C-reactive protein as a Predictor of Early Outcome Following Acute Myocardial Infarction (Bangladesh Journal of Medicine, 2021)
Background: Acute myocardial infarction (AMI) which constitutes STEMI & NSTEMI triggers an inflammatory reaction, which plays an important role in myocardial injury. An inflammatory marker such as C - reactive protein (CRP) reflects the extent of myocardial necrosis.Circulatory levels of Creactive protein (CRP) may be an independent risk factor for cardiovascular disease.Methods: An observational study was carried out in the department of Medicine and department of Cardiology of Faridpur Medical CollegeHospital, Faridpur from May 2012 to October 2012. One Hundred Patients were selected consecutively from acute Myocardial Infarction patients admitted in the department of medicine and Department of Cardiology of Faridpur Medical College Hospital. The sample was selected purposively. Quantitative value of CRP was done on first day of admission. Z test of proportion was done to analyze the data. Level of significance was < 0.05.Results: In this study, 84% of AMI had CRP level >6 mg/dl.86% patients had STEMI, and 14% patients had NSTEMI. Out of 86 patients with STEMI, 72 patients (83.72%) & out of 14 patients with NSTEMI, 12 patients (85.71%) had high CRP. Out of 72 STEMI patients with high CRP level, 22 patients (30.55%) & 6 patients (8.33%) were expired. Out of 12 NSTEMI patients with high CRP level, 2 patients (16.67%) developed left ventricular failure&no one was expired. STEMI was associated with worst outcome 30.55% vs 16.67% left ventricular failure and 8.33% vs 0% mortality rate.Conclusions: High CRP is a predictor of adverse early outcome in patients with acute coronary syndromesBangladesh J Medicine July 2021; 32(2) : 95-98